The five-year results of the Birmingham Hip Resurfacing arthroplasty: an independent series. - Steffen, RT; Pandit, H; Palan, J; Beard, D; Gundle, R; McLardy-Smith, P; Murray, D; Gill, H (2008)
Few independent studies have reported the outcome of resurfacing arthroplasty of the hip. The aim of this study was to report the five-year clinical outcome and seven-year survival of an independent series. A total of 610 Birmingham Hip Resurfacing arthroplasties were performed in 532 patients with a mean age of 51.8 years (16.5 to 81.6). They were followed for between two and eight years; 107 patients (120 hips) had been followed up for more than five years. Two patients were lost to follow-up. At a minimum of five years' follow-up, 79 of 85 hips (93%) had an excellent or good outcome according to the Harris hip score. The mean Oxford hip score was 16.1 points (sd 7.7) and the mean University of California Los Angeles activity score was 6.6 points (sd 1.9). There were no patients with definite radiological evidence of loosening or of narrowing of the femoral neck exceeding 10% of its width. There were 23 revisions (3.8%), giving an overall survival of 95% (95% confidence interval 85.3 to 99.2) at seven years. Fractured neck of femur in 12 hips was the most common indication for revision, followed by aseptic loosening in four. In three hips (three patients) (0.5%), failure was possibly related to metal debris. Considering that these patients are young and active these results are good, and support the use of resurfacing. Further study is needed to address the early failures, particularly those related to fracture and metal debris.